Role of Integrated Child Development Services (ICDS) Program in Early Childhood Care vis-a- vis Human Development: A Micro Level Study in Kerala, India (Journal of Governance and Development (JGD), 2014)
The ICDS Program has remained in the forefront of the efforts of the Government of India (GoI) and the State Governments to achieve the child nutrition related Millennium Development Goal (MDG1). However, more attention has been given to increase coverage than to improve the quality of service delivery and to distribute food rather than changing family-based feeding and caring behavior. The present study attempts to examine the role of ICDS by analyzing the success in improving nutritional status of children and the effectiveness of Preschool education. The study is based on the findings of a one month field survey conducted in Vallachira Panchayath in Thrissur District. Z scores for Weight for age, height for age and weight for height are used to assess the nutritional status of the children. The result reveals that low coverage of eligible beneficiaries is the major problem faced by the ICDS in the study area. But ICDS provide better service to the beneficiaries who enrolled in AWC. It remains successful in improving the nutritional status in the study area. It also finds that the program has a positive impact on the preschool education of ICDS children. In addition, there is a need to achieve better community participation and awareness about the program. Therefore the study suggests a multipronged approach to address community involvement in ICDS.